Inter-observer and intra-observer variability in the assessment of the paranasal sinuses radiographs - Kamarudin, Norie Azilah; Raja Lope Ahmad, Raja Ahmad Al'konee; Liew, Wai Fong; Mohamed, Zahiah (Internet Scientific Publications, 2006)
The aims of this study are to determine the intra-observer and inter-observer agreement between the two radiologists when reporting the Waters view and 3 views series of the paranasal sinus radiographs. To also determine whether a single Waters view is adequate for diagnostic purpose of sinusitis. 90 sets of paranasal sinuses radiographs were reported by two radiologists independently. The results revealed that the intra-observer and inter-observer agreement varied from almost perfect to good for maxillary and frontal sinuses, but poor for sphenoid and ethmoidal sinuses. Therefore, a single waters view is an acceptable strategy for diagnosing sinusitis for the maxillary and/or frontal sinuses but not for the ethmoid and sphenoid sinuses.